COMMUNICATION AS A SOLUTION OF A CONFLICT BETWEEN PARENTS AND ADOLESCENTS OF DRUG USERS IN DONGGALA REGENCY - ASTUTY (CV KULTURA DIGITAL MEDIA, 2021)
One of the inherent traits of youth is the desire to dabble in new things. This desire is not accompanied by good self-control so that teenagers can fall into negative things such as being drug users. This can have an impact on the future and an incoherent relationship with parents. The method uses qualitative research with data collection techniques with in-depth observations and interviews. The results showed that the attitude of teenagers in Donggala Regency can be antagonistic, not listen to the advice of parents and perform physical acts on parents and become thieves in their own homes and in the surrounding environment because the teenagers have become drug users. This has an impact on the disharmonious relationship between parents and adolescents. Therefore, as parents should be able to communicate dialogically to adolescents with the aim to change their attitudes and behaviors in order to become aware and willing to do the rehabilitation process.